Aplikasi Cerdas Berbasis Android Untuk Diagnosa Penyakit Paru-Paru Pada Pecandu Rokok Dengan Metode Forward Chaining - Rendi Eka Putra; Dian Eka Putra (Jurnal TEFSIN ( Jurnal Teknik Informatika dan Sistem Informasi), 2024)
The rapid development of information technology in the world, including in Indonesia, has resulted in many countries taking advantage of this opportunity to increase effectiveness and efficiency in various fields such as defense and security, government, economics, social politics, culture and health. Along with high levels of mobility, many countries are creating smart devices, one of which is the smartphone (smartphone). Smartphones are electronic handheld gadgets that include advanced functionality beyond making phone calls and sending text messages. This explains that smartphones have certain advantages in providing services to their users such as iPhones or other Android-based cellphones, which can run third-party applications by providing unlimited functionality. A framework for thinking is a clear description of the discussion that will resolve until a good solution is obtained. produced an Android application to diagnose lung disease in cigarette addicts. From the analysis and discussion that has been carried out in the previous chapters, the author can draw the conclusion that: Can be used to gain knowledge about lung disease in cigarette addicts from the symptoms. This expert system application has a simple appearance and is easy for users to understand. This application is also light and does not require an expensive smartphone to use.